The Influence of Social Media Marketing On Purchase Decisions - Juharsah; Hartini (International Journal of Management and Education in Human Development, 2022)
This study aims to determine the effect of social media marketing, which consists of content creation, sharing, connecting, and community building on purchasing decisions. The population in this study were all Instagram social media followers from handicraft businesses in Kendari City, the number of samples was 96 respondents who were determined using the gameshow formula, and the model used the conventional method. The data obtained were then analyzed by multiple linear regression analysis obtained using SPSS software version 26.0. The results of the research show that content creation, content sharing, connecting, and community building have a significant effect on purchasing decisions.